Contractual liabilities in software transactions: an overview (2009)
Software technology has taken an important position in the information technology environment. Basically, computing equipment may be useless without putting the softwares to drive it in place. The development of software has therefore taken a centre stage in the information technology market. The importance of computer in the society cannot be underestimated, as virtually all organizations, trades and professions cannot operate efficiently without having something to do with computers. Most of these organizations, trades and profession sometimes need customized softwares to drive their computers. No' doubts, software development seems to be a money making ventures, especially for experts in this field. However, this juicy advantage may turn into a daunting nightmare for unguarded software developer who may not understand the legal terrain in which he operates. It is on this note that the probable liabilities software developers may incur in the process of plying his trade are discovered and discussed in this work.